2020
DOI: 10.1007/s12630-020-01615-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morbid obesity or advanced maternal age on oxytocin-induced myometrial contractions: an in vitro study

Abstract: The purpose of this study was to investigate myometrial contractility induced by oxytocin in women with advanced maternal age (AMA) and morbid obesity (MO). We hypothesized that both oxytocinpretreated and oxytocin-naïve myometrial tissues from women of AMA and women who are MO would exhibit poor myometrial contractility compared with women that are younger and of normal body mass index (BMI). Methods This prospective in vitro study was conducted using myometrial samples obtained from women undergoing elective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Obesity itself appears to reduce myometrial contractility and confer a blunted response to oxytocin [18]. Recent in‐vitro research from our own group indicates that myometrial strips obtained from women with a BMI ≥ 40 kg.m ‐2 undergoing elective caesarean delivery contract with less force and lower frequency than those of women of a normal weight [19]. The biological processes underpinning these findings are uncertain, and many mechanisms have been proposed [18,35–37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity itself appears to reduce myometrial contractility and confer a blunted response to oxytocin [18]. Recent in‐vitro research from our own group indicates that myometrial strips obtained from women with a BMI ≥ 40 kg.m ‐2 undergoing elective caesarean delivery contract with less force and lower frequency than those of women of a normal weight [19]. The biological processes underpinning these findings are uncertain, and many mechanisms have been proposed [18,35–37].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal obesity may increase the risks of PPH and uterine atony [14][15][16][17][18], and may be associated with an increased risk of death in women with PPH [2]. The reasons behind these observations remain unclear, although impaired myometrial contraction in response to oxytocin may play a role [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical and translational studies have suggested a decrease in uterine contractility among obese and morbidly obese women. [24][25][26] Uterine contractility plays an important role in postdelivery uterine involution; impaired contractility can contribute to PPH. Should contractility be impaired among obese women, there would be implications for management.…”
mentioning
confidence: 99%
“…In addition, to achieve vaginal delivery, obese women require more concentration, higher doses, and longer duration of exposure of uterotonics medication, using similar protocol and guidelines on labor induction for all women with different BMI to end up with higher failure rate among obese women [ 44 , 45 ]. The current study has been shown that uterine contractility impairment is higher among morbid obesity women; uterine contractility dysfunction might lead to failed induction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%